PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE (TPS) DALAM MENINGKATKAN HASIL BELAJAR FISIKA SISWA KELAS X-2 SMA NEGERI 3 KENDARI - Suparman . (Jurnal Aplikasi Fisika, 2016)
A classroom action research has been successfully performed to improve learning achievement teaching and learning in the class X-2 of SMAN 3 Kendari . This research is used to answer the question whether student understanding can be enhanced through cooperative learning think-pair-share model . To answer these problems, so in this study focused on students as the main subject. Researcher examines the interests and abilities of students in studying physics through cooperative learning model think-pair-share especially when studying the subject of linear motion with constant velocity and acceleration. The results showed that under evaluation or test the cycle II exhibit that the results of learning physics class X-2 SMAN 3 Kendari increased when compared with the cycle I. Student learning outcomes in classical physics in the first cycle of 60.16 while on  cycle II reached 72.09. By evaluating the results obtained in the second cycle means learning achievement physics students has increased, the study was stopped in the cycle II. Eventhough the  subject of linear motion with constant velocity and acceleration of unfinished taught. Indicators of success has been achieved in this research is at least 80% of students have reached a value ³ 65. Nevertheless, the process of teaching and learning in the classroom to continue until the completion of the subject rectilinear motion with constant velocity and acceleration. Thus, the hypothesis that the action has been achieved by using cooperative learning model think-pair-share, academic achievement of physics class X-2 SMAN 3 Kendari on the subject of linear motion with constant velocity and acceleration can be improved.